The Effects Of ND: Yag Laser Capsulotomy On Intraocular Pressure In Diabetic Patients - Umer, Seher; Zubair, Maria; Rasool, Wajeeha; Jamil, Ameera; Mohsin, Maimoona; Niazi, Fuad Ahmed Khan (Journal of Rawalpindi Medical College, 2025)
Objective: To determine the mean intraocular pressure (mean IOP) changes after Nd: YAG laser capsulotomy for posterior capsule opacification (PCO) and to compare IOP in diabetic and non-diabetic patients after Nd: YAG laser capsulotomy. Methods: Total 200 patients of all genders between 26 and 60 years of age who have undergone cataract surgery within 6 months to 3 years prior were included and were treated with minimum possible pulses of Nd: YAG with an energy of 1-13 ml/pulse and capsulotomy with an opening of 3.0-4.0mm of diameter in posterior capsule. After the laser, the intraocular pressure was measured at 1 hour, 2 hours, 4 hours and 24 hours. An independent t-test was used to compare the mean intraocular pressure between two groups at first hour, 2 hours, 4 hours, 24 hours and one week time points. A paired t-test was used to compare the mean difference in IOP from baseline at each post-Laser interval in each group, respectively. Results: Out of 200 patients (200 eyes), 100 patients (50%) were diabetic and 100 patients (50%) were non-diabetic. The mean pre-laser IOP was 14.72 ± 2.67 in the diabetic group and 14.36 ± 1.47 in the non-diabetic group. At one hour after laser treatment, the mean IOP was 19.17 ± 3.16 in the diabetic group and 15.62 ± 2.33 in the non-diabetic group, with p p-value of 0.0001. Mean intraocular pressure difference at 1st hour is 3.55 mmHg in the diabetic group, which is significantly higher than that in the non-diabetic group, which is 1.26 mmHg. Conclusion: This study concluded that IOP rises at the 1st and 2nd hour after Nd: YAG capsulotomy, and after that it gradually decreases to prelaser values after 24 hours. The mean intraocular pressure difference at 1st hour in the diabetic group is significantly higher than that in the non-diabetic group